EVALUASI KARAKTERISTIK FISIKA-KIMIA SEDIAAN KRIM DAN LOTION EKSTRAK KULIT BUAH NANAS (Ananas comosus L.Merr) - Elya Zulfa; Mufrod Mufrod (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2018)
ABSTRACTIn previous research, ethanolic extract of pineapple peel (EEPP) has activity as a sunscreen because of the content of flavonoids. EEPP can be formulated in the form of creams and lotions to facilitate use on the skin. This study aims to evaluate the physical chemistry characteristics of EEPP creams and lotions. Creams and lotions were made in 3 formulas based on variations in FI extract concentrations (15.0%), FII (17.5%), FIII (20.0%), base controls and positive controls (preparations on the market). The cream obtained was evaluated for physical chemical characteristics including organoleptic, homogeneity, adhesion and dispersion, viscosity, pH and SPF values which were analyzed descriptively. cream with varying concentrations of green, the distinctive smell of pineapple, homogeneous and in accordance with the pH of the skin. Increasing the concentration of EEPP in the preparation has an effect on increasing viscosity, adhesion but decreasing the dispersion. Whereas the lotion shows greenish color, aromatic odor and semisolid texture and is easily applied. The increase in EEPP in lotion affects the increase in pH, adhesion, but decreasing the dispersion.Keywords: Creams, lotions, sunscreen, pineapple fruit skin